Analisis Bauran Pemasaran Usaha Industri Batu Bata Pak Mandor di Kelurahan Danau Balai Kabupaten Labuhanbatu - Kurniawan, Deni; Simanjorang, Elida Florentina Sinaga (Universitas Labuhanbatu, 2024)
Bricks are one of themost important materials in residential and construction buildings. Bricks are also included as micro, small and medium enterprises, some of which provide employment opportunities for to community to earn daily income. The success of a company also depends on the marketing mix. A company with a lot of sales certainly has good and planned marketing. Danau balai subdistrict is a brick manufacturing area in labuhanbatu district. 60% of the need for bricks in labuhanbatu is supplied from Rantau Selatan sub-district and around 40% is taken from Asahan and north labuhanbatu district. The four components of the marketing mix itself are 4P (product, price, promotion, distribution). The concept of this strategy is to increase sales and achieve the goals you want to achieve as well as provide the best service for costumers. We can conclude that marketing strategy is very important in this business.This type of research is qualitative research using observation, interviews and documentation methods. The data source for this research is the resulst of interviews with brick industry business owners. The result is to find out what marketing mix strategy this brick business has.